PENGARUH INTELLECTUAL CAPITAL TERHADAP PRODUKTIVITAS DAN NILAI PERUSAHAN PADA PERUSAHAN PERBANKAN - Adhitama, Muhammad Yusuf; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTIntellectual capital is a concept in assessing the financial performance that has developed rapidly in recent years. Currently there are some companies which have not reported the occurrence of intangible asset such as intellectual capital particularly human capital which has contribution in creating competitive advantage in winning a very competitive competition. This purpose of this research is to examine the influence of intellectual capital to the productivity and the firm value. The population is all banking companies. The samples have been selected by using purposive sampling technique so 21 banking companies which have met criteria have been selected as samples. The analysis technique has been done by using simple linear regression equation analysis. The result of the examination shows that intellectual capital give positive influence to the productivity. This means that the enhancement of intellectual capital can benefit the company and become the potential element in enhancing the company productivity. The result of the test shows that intellectual capital give positive influence to the firm value. This can be possible because of the intellectual capital which has been allocated by the company is getting large, so it can increase the firm value.Keywords: intellectual capital, productivity, firm value.